2021
DOI: 10.1002/mabi.202100375
|View full text |Cite
|
Sign up to set email alerts
|

HER2‐Targeted, Degradable Core Cross‐Linked Micelles for Specific and Dual pH‐Sensitive DOX Release

Abstract: Here, a targeted, dual‐pH responsive, and stable micelle nanocarrier is designed, which specifically selects an HER2 receptor on breast cancer cells. Intracellularly degradable and stabilized micelles are prepared by core cross‐linking via reversible addition−fragmentation chain‐transfer (RAFT) polymerization with an acid‐sensitive cross‐linker followed by the conjugation of maleimide–doxorubicin to the pyridyl disulfide‐modified micelles. Multifunctional nanocarriers are obtained by coupling HER2‐specific pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For example, Savic et al reported the loss of PCL- b -PEO micelle integrity after 1 h of intramuscular or subcutaneous injection . Therefore, recent research have been focused on novel approaches to increase the stability of micelles, and the cross-linking approach has proven to be highly efficient for this purpose. , The cross-linking approaches reported so far include core-cross-linking, shell cross-linking, , and cross-linking at the shell–core interface . Together with improving the structural ability of micelles, cross-linking can also control the rate of drug release .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Savic et al reported the loss of PCL- b -PEO micelle integrity after 1 h of intramuscular or subcutaneous injection . Therefore, recent research have been focused on novel approaches to increase the stability of micelles, and the cross-linking approach has proven to be highly efficient for this purpose. , The cross-linking approaches reported so far include core-cross-linking, shell cross-linking, , and cross-linking at the shell–core interface . Together with improving the structural ability of micelles, cross-linking can also control the rate of drug release .…”
Section: Introductionmentioning
confidence: 99%
“…10 Owing to the versatility of RAFT polymerization, it is possible to obtain cross-linked micelles during copolymerization and improve the functionality for further modifications. 8,9 The main concept to obtain a stable and multifunctional micelle-based nanocarriers relies on using a hydrophilic polymer in the shell part, while other components are used for the core part together with a specific cross-linker. Also, using polymers with the LCST or UCST behavior reveals temperature sensitivity that can be utilized for controlled delivery of the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking in the micelle structure has been proposed in the last decade as a way to prevent early micelle dissociation and premature drug release. , They can be designed as environmentally degradable or hydrolyzable systems at low pH or reductive conditions, which can lead to time- or site-controlled release of bioactive agents . Owing to the versatility of RAFT polymerization, it is possible to obtain cross-linked micelles during copolymerization and improve the functionality for further modifications. , The main concept to obtain a stable and multifunctional micelle-based nanocarriers relies on using a hydrophilic polymer in the shell part, while other components are used for the core part together with a specific cross-linker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric self-assemblies such as vesicles and micelles prepared from amphiphilic copolymers have shown encouraging results as chemotherapeutic nanocarriers due to their distinct shell-core nanostructures [1,2]. The hydrophobic blocks of micellar cores can entrap and solubilize hydrophobic drugs [3,4]. In addition, hydrophilic coronas can efficiently protect the hydrophobic core and their entrapped therapeutics from the external biological environment during blood circulation to diminish the nonspecific adsorption by protein [5][6][7].…”
Section: Introductionmentioning
confidence: 99%